2023
DOI: 10.3390/bs13040345
|View full text |Cite
|
Sign up to set email alerts
|

Career Calling, Courage, Flourishing and Satisfaction with Life in Italian University Students

Abstract: Career calling is defined as a positive resource promoting vocational development and well-being. The present study focuses on the relationships between career calling, courage and two indicators of well-being, i.e., flourishing and satisfaction with life. The sample consisted of 306 Italian university students (118 males and 188 females) ranging from 18 to 30 years of age. A structural equation modeling (SEM) approach with latent variables was adopted. The results showed that courage plays a mediating role be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…In other terms, they seem to pursue fields that align with their hobbies, talents, and areas of expertise, as they derive satisfaction from doing what they like. Several studies have found that people are strongly motivated to pursue careers that align with their passions [40] or vocation [41]. According to the narratives, participants seem to prioritize their vocations over potential salary.…”
Section: Discussionmentioning
confidence: 97%
“…In other terms, they seem to pursue fields that align with their hobbies, talents, and areas of expertise, as they derive satisfaction from doing what they like. Several studies have found that people are strongly motivated to pursue careers that align with their passions [40] or vocation [41]. According to the narratives, participants seem to prioritize their vocations over potential salary.…”
Section: Discussionmentioning
confidence: 97%
“…This divine connection disappeared, but the concept of calling remained in the literature with the meaning of a relationship with work marked by a strong internal source that drives towards a certain work (Wrzesniewski et al 1997). The concept of career calling has been widely used in the literature (Chen et al 2023;Cai et al 2021;DiRenzo et al 2022;Parola et al 2023;Shang et al 2022) and represents a perfect fit between work and an individual's identity and sense of destiny or inevitability (Duffy et al 2014;Pitacho et al 2019a). In career calling, a professional occupation is an extension of an individual themself, of their values and interests.…”
Section: Introductionmentioning
confidence: 99%